Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12909-020-02267-2
|View full text |Cite|
|
Sign up to set email alerts
|

What is the impact of the COVID-19 pandemic on emergency medicine residency training: an observational study

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic has engendered difficulties for health systems globally; however, the effect of the pandemic on emergency medicine (EM) residency training programs is unknown. The pandemic has caused reduced volumes of emergency department (ED) patients, except for those with COVID-19 infections, and this may reduce the case exposure of EM residents. The primary objective of this study was to compare the clinical exposure of EM residents between the prepandemic and p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 27 publications
(23 reference statements)
0
34
0
Order By: Relevance
“…However, the training of ED residents may become a problem due to the decreased volume of patients. Lo et al 19 reported that the average number of pediatric patients managed by residents decreased from 1.56 to 0.51 during the pandemic. To maintain the quality of ED resident training, new education programs should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, the training of ED residents may become a problem due to the decreased volume of patients. Lo et al 19 reported that the average number of pediatric patients managed by residents decreased from 1.56 to 0.51 during the pandemic. To maintain the quality of ED resident training, new education programs should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has led to several changes in airway management. These changes can have a potentially negative impact on the training of less experienced physicians, especially junior residents [ 21 ]. For example, recent airway management guidelines for patients with confirmed or suspected COVID-19 advocate ETI being performed by the most experienced physician to increase the FPS rate [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lo et al studied the impact of COVID-19 pandemic on emergency medicine residency training. They noticed a reduced emergency department volume and decreased residents' clinical exposure and advised to adjust the training programs and utilize ancillary methods of learning to ensure adequate training [ 20 ]. In pathology, Stathonikos et al discussed in their review some measures that they followed to improve this, including utilization of digital pathology in training [ 19 ].…”
Section: Discussionmentioning
confidence: 99%